SEMIOTIC ANALYSIS OF THE BEBUANG TRADITIONAL RITUAL OF THE LIPAN ISLAND SEA TRIBE COMMUNITY, PENUBA VILLAGE, SELAYAR DISTRICT, LINGGA REGENCY: Analisis Semiotik Ritual Adat Bebuang Masyarakat Suku Laut Pulau Lipan Desa Penuba Kecamatan Selayar Kabupaten Lingga - Rahma Andani; Ahada Wahyusari; Dody Irawan; Abdul Malik; Isnaini Leo Shanty; Tessa Dwi Leoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses the Semiotic Analysis of Bebuang Traditional Rituals of The Sea Tribe Community of Lipan Island, Penuba Village in Selayar district, Lingga Regency. This research method is descriptive analysis using a qualitative approach and applying semiotic theory and Charles Sanders Peirce. The data collection techniques used are participant observation, in-depth interviews and documentation. The data analysis technique in this study uses qualitative analysis techniques. The results of the data analysis obtained from the Semiotic Analysis of Bebuang Traditional Rituals of The Sea Tribe Community of Lipan Island, Penuba Village in Selayar district, Lingga Regency show that the Bebuang mantra contains linguistic and symbolic signs that reflect the spiritual, social, and ecological values of the Sea Tribe community. The semiotic meaning in the Bebuang mantra not only plays a role as a means of communication with ancestral spirits, but also as a form of local wisdom that strengthens the cultural identity of the Sea Tribe community.